RETROSPECTIVE STUDY OF THE EFFICACY OF LONG-TERM TREATMENT OF FELINE IDIOPATHIC CYSTITIS - Anca Bărbos; Vlad Luca; Alexandra Biriș; Radu Lăcătuș (Agricultura)
The aim of our research was to determine the efficacy of long-term treatment of feline idiopathic cystitis. For this purpose, a population of 42 cats suffering from feline idiopathic cystitis was selected and divided into two groups. Group A, consisting of 28 cats, represents cats whose environment was enriched by the method of multimodal environmental modification (MEMO). Group B, consisting of 14 cats, representing cats whose environment has not been modified at all. Most cats affected by this pathology were neutered males (70%), Domestic ShortHair breed, middle aged (with a mean of 9 years for group A and approximately 8 years and 2 months for group B), overweight and mostly living indoors (80.95%). Most of our patients presented after a triggering event (64.29%) with symptoms such as pollakiuria (75%), stranguria (78.57%), excessive toileting of the pelvic area (75%) and periuria in 71.43% of cases. During the acute episode most cats received analgesics (92.86%), antibiotics (82.14%), anti-inflammatories (71.43%), antidepressants and sympatholytics with improvements in 82.14% of cases. Despite the improvement in the general condition of the cats, relapses occurred in 71.43% of cases in group A and in 64.29% of cases in group B. Felines in group A receive food supplements (hydrolysed milk proteins, corn silk, D-mannose, Cosequin®, N-acetyl glucosamine) in 53.57% of cases compared to 42.86% of cases in group B. Group B, in which multimodal environmental modification (MEMO) was not used, showed an improvement in the condition of the cats in 35.71% of cases, but with frequent relapses following drug treatment and the use of pheromones in the house. Group A shows an improvement in the condition of the cats in 46.43% due to the implementation of the MEMO method and the use of drug treatment and pheromones, however the number of relapses remains high.